Advanced Biomaterials and Biodevices 2014
DOI: 10.1002/9781118774052.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as an Advanced Healthcare Material

Abstract: Chitin and chitosan are renewable biopolymers with inherently favourable properties allowing diverse chemical modifi cation that generates novel materials ideal for biomedical applications. Chitin itself has very poor aqueous solubility and hence found limited utility. For this reason the use of chitosan, in particular, modifi ed chitosan, has increased exponentially in biomedical applications in recent years. Th e review of chitosan as a health care material includes wound healing or tissue regeneration, drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 126 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…demonstrated that the presence of a quaternary ammonium functionality in a resin improved retention [ 34 ]. Chitosan in its native form is positively charged as the amino group present has a pKa of ~6.5; therefore, the polymer can bind to negatively charged ions such as [ 35 ]. Protonated chitosan in an acidic medium has been shown to remove from solution [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that the presence of a quaternary ammonium functionality in a resin improved retention [ 34 ]. Chitosan in its native form is positively charged as the amino group present has a pKa of ~6.5; therefore, the polymer can bind to negatively charged ions such as [ 35 ]. Protonated chitosan in an acidic medium has been shown to remove from solution [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ideal structure of chitosan, as a primary derivative of chitin, is based on linear repeating units of β-(1-4)-2-amino-2-deoxy-D-glucopyranose, in which the acetylated units of N-acetyl-D-glucosamine of the chitin are deacetylated to become D-glucosamine units [ 34 ]. The functionality of this cationic biopolymer provided by the two hydroxyl groups (at C3 and C6) and one amine group (at C2) allows extensive adjustment of physical, chemical, mechanical and biological properties [ 35 ].…”
Section: Introductionmentioning
confidence: 99%